PENGARUH KUALITAS PRODUK, HARGA DAN PERSAINGAN TERHADAP MINAT BELI - Halim, Nico Rifanto; Iskandar, Donant Alananto (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
The purpose of this research is to understand the influence of product quality, price and competition on interest in buying Nadja Brown Sugar products. This research is a quantitative study using SPSS Statistics 22 program with a total sample of 120 respondents who are customers and consumers of Nadja Red Sugar in DKI Jakarta who have bought and used Nadja Brown Sugar as much as one or more times using non probability sampling and convenience sampling techniques . The results of this study show that the three variable variables that have no significant effect on buying interest The implications of this study can be a reference for business owners in formulating a strategy to increase interest in buying Nadja Red Sugar products related to product quality, price and competition.products related to product quality, price and competition. Keywords: product quality, price, competition and interest in buying